Towards a New Balance: The Role of the DPD in Indonesian Democracy - Suyitno, Imam; Ridhoh, M. Yunasri; Aba, Akbar; Maryati, Maryati (Universitas of Muhammadiyah Makassar, 2024)
This article focuses on the problem that the role of the Regional Representative Council (DPD) in the dynamics of democracy in Indonesia is experiencing an imbalance in its relationship with the government and other people's representative institutions such as the People's Representative Council (DPR). The research methods used include literature studies, conceptual analysis, case studies, and document analysis. With a qualitative approach and descriptive analysis, this research aims to understand the role that the DPD should play in the dynamics of Indonesian democracy. The research results show that the practice of democracy in Indonesia has experienced ups and downs from tyranny to anarchy, and vice versa, namely conditions that are not ideal and unbalanced (disequilibrium). To achieve true democracy, efforts are needed to create a new balance between the government and people's representative institutions, by giving power to the DPD in the legislative process, as well as giving the DPD the authority to nominate candidates for President and Vice President.